For quantitative criteria in alien species assessment - Sandvik, Hanno (Frontiers in Environmental Science, 2023)
Impact or risk assessments of alien species can use qualitative criteria (such as verbally described categories) or quantitative criteria (numerically defined threshold values of empirically measurable quantities). According to a common misconception, the use of qualitative criteria in invasion biology is justified by uncertainty in the available data. Yet qualitative criteria have the effect of increasing uncertainty. In contrast, assessments using quantitative criteria are testable, transparent, highly repeatable and comparable. Most of these characteristics do not even depend on the availability of numerical data. Although quantitative criteria do not necessarily make assessments correct, they do make them correctable, which is the benchmark of science.